2017
DOI: 10.1002/mdc3.12493
|View full text |Cite
|
Sign up to set email alerts
|

A History of Dystonia: Ancient to Modern

Abstract: Before 1911, when Hermann Oppenheim introduced the term dystonia, this movement disorder lacked a unifying descriptor. While words like epilepsy, apoplexy, and palsy have had their meanings since antiquity, references to dystonia are much harder to identify in historical documents. Torticollis is an exception, although there is difficulty distinguishing dystonic torticollis from congenital muscular torticollis. There are, nevertheless, possible representations of dystonia in literature and visual art from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 46 publications
0
33
0
2
Order By: Relevance
“…The subtle boundary between the two favoured the development of conflicting theories about aetiology and pathogenesis of certain disorders. This is true for dystonia which, at the time of the schism, was retained amongst organically unaligned or functional conditions and then classified as a motor neurosis (Newby et al 2017). David Marsden, with his brilliant intuition, removed dystonia from this unclear classification and recognized it as a basal ganglia (BG) disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The subtle boundary between the two favoured the development of conflicting theories about aetiology and pathogenesis of certain disorders. This is true for dystonia which, at the time of the schism, was retained amongst organically unaligned or functional conditions and then classified as a motor neurosis (Newby et al 2017). David Marsden, with his brilliant intuition, removed dystonia from this unclear classification and recognized it as a basal ganglia (BG) disorder.…”
Section: Introductionmentioning
confidence: 99%
“…If so, this highlights a gap in the existing research: we need to know more about the nature of the connection between physical and mental states and handwriting. In fact, the boundary between "physical" and "mental" states, itself, is not clear, since there is currently active discussion among neurologists about what comprises a "psychiatric" disorder versus a "neurological" disorder-with some that have been previously labelled "disorders of the mind" being recently re-classified as having possible organic causation (Newby et al 2017). Thus, the final section of this chapter demonstrates how academics are finally moving to fill this gap, going "back to basics" with their inquiries into individual difference and handwriting features.…”
mentioning
confidence: 99%
“…We read with interest the paper by Newby at al., published recently in MDCP, "A History of Dystonia: Ancient to Modern," about Modigliani's "Portrait of Jeanne Hebuterne in a Large Hat." 1 In fact, we had previously suggested that this painting showed an example of a sensory trick for cervical dystonia (Supporting Figure S1). 2 Now, here we share further evidence to confirm that this lady, common-law wife, and muse of the painter indeed had cervical dystonia.…”
mentioning
confidence: 82%